2007
DOI: 10.1074/jbc.m610253200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inositol 1,4,5-Trisphosphate 3-Kinases by Calcium and Localization in Cells

Abstract: We also compared the effects of the these IP 3 Ks with other enzymes that metabolize Ins(1,4,5)P 3 , including the Type I Ins(1,4,5)P 3 5-phosphatase, in both membrane-targeted and soluble forms, the human inositol polyphosphate multikinase, and the two isoforms of IP 3 K found in Drosophila. All reduce the Ca 2؉ signal but to varying degrees. We demonstrate that the activity of only one of two IP 3 K isoforms from Drosophila is positively regulated by calmodulin and that neither isoform associates with the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 68 publications
1
34
0
Order By: Relevance
“…, all three human isoforms bind calmodulin (CaM) in a Ca 2? -dependent manner, via a conserved domain [45]. The three human isoforms of ITPK show diversity in their N-termini [8].…”
Section: )P 3 Onlymentioning
confidence: 99%
See 3 more Smart Citations
“…, all three human isoforms bind calmodulin (CaM) in a Ca 2? -dependent manner, via a conserved domain [45]. The three human isoforms of ITPK show diversity in their N-termini [8].…”
Section: )P 3 Onlymentioning
confidence: 99%
“…The L34P mutation destroys F-actin binding in ITPKA [133], while L139P and L159P reduce F-actin binding in ITPKB [77]. The W167R mutation destroys CaM binding in ITPKA; analogous mutations behave similarly for ITPKB and C [45]. Arrowheads in the blue and gray areas point to two of the many mutations in the active site that destroy catalytic activity [21].…”
Section: )P 3 Onlymentioning
confidence: 99%
See 2 more Smart Citations
“…Like dematin, IP3KB is ubiquitously expressed and was recently shown to be enriched within the cortical actin filaments (53). It has been suggested that the localization of IP3KB may offer a means to regulate IP 3 levels in the cells (36,54). However, the precise mechanism of IP3KB localization at the membrane sites via cortical actin structures is not known (53).…”
Section: Discussionmentioning
confidence: 99%